2023
DOI: 10.1111/jce.15981
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of first‐ and second‐generation leadless pacemakers in patients with sinus rhythm and complete atrioventricular block

Abstract: IntroductionThe efficacy and safety of leadless cardiac pacemakers (LPMs) as an alternative to conventional transvenous cardiac pacing have been largely reported. The first generation of the MicraTM transcatheter pacing system (VR; Medtronic) was able to provide single‐chamber VVI(R) pacing mode only, with a potential risk of pacemaker syndrome in sinus rhythm patients. A second‐generation system (AV) now provides atrioventricular synchrony through atrial mechanical (Am) sensing capability (VDD mode).Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although the number of patients eligible for LP has increased substantially with the introduction of LPs featuring atrial synchronization, careful evaluation of the procedural complexity is increasingly vital in the selection between LP and transvenous pacemakers to avoid complications. 19 , 20 , 21 Considering the present results, transvenous pacemakers may be an acceptable option for patients exhibiting RV dilation or severe TR. Nonetheless, it is noteworthy that although 2 cases in our study showed threshold elevation during or after LP implantation, no major complications, including pericardial effusion or cardiac tamponade, were reported.…”
Section: Discussionmentioning
confidence: 72%
“…Although the number of patients eligible for LP has increased substantially with the introduction of LPs featuring atrial synchronization, careful evaluation of the procedural complexity is increasingly vital in the selection between LP and transvenous pacemakers to avoid complications. 19 , 20 , 21 Considering the present results, transvenous pacemakers may be an acceptable option for patients exhibiting RV dilation or severe TR. Nonetheless, it is noteworthy that although 2 cases in our study showed threshold elevation during or after LP implantation, no major complications, including pericardial effusion or cardiac tamponade, were reported.…”
Section: Discussionmentioning
confidence: 72%
“…17 Other authors found that a mitral E/A ratio lower than 1.2 appears to be an echocardiographic independent predictor of high AV synchrony. 14 According to our preliminary data morphological parameters such as LA APD and LAV, both as absolute values and indexed by body surface area, are related to different A4 vectorial sum. However, there is growing evidence that LA remodeling is not equal to LA enlargement alone as it includes LA changes at the molecular, cellular and tissue level even before LA enlargement.…”
Section: Discussionmentioning
confidence: 93%
“…Difficulty in AVS assessment is a recent topic of discussion and many efforts have been made to improve LCPM programming and achieve a higher rate of AVS. 13,14 Alongside this, we believe it is important to focus attention on the selection of patients, that could be crucial to optimize the choice of pacing device, based on echocardiographic parameters. Our data showed a statistically significant relationship between echocardiographic parameters, like APD, LAV and LAs, and atrial contraction signal The MASS and MASS2 study first demonstrated the feasibility of tracking mechanical atrial activity to provide AVS.…”
Section: Discussionmentioning
confidence: 99%
“…As this patient continues to become more active, further adjustment of atrioventricular synchrony can be performed with generation one Micra AV devices having a median synchrony of 78%, while generation two devices are likely to have a higher amount of synchrony. 6 Predicted longevities of devices may also account for choice of leadless option and/or other atrial pacing modalities.…”
Section: Discussionmentioning
confidence: 99%